Studies on a Double Poisson-Geometric Insurance Risk Model with Interference - Yujuan Huang; Wenguang Yu (Discrete Dynamics in Nature and Society)
This paper mainly studies a generalized double Poisson-Geometric insurance risk model. By martingale and stopping time approach, we obtain adjustment coefficient equation, the Lundberg inequality, and the formula for the ruin probability. Also the Laplace transformation of the time when the surplus reaches a given level for the first time is discussed, and the expectation and its variance are obtained. Finally, we give the numerical examples.